Aluminum methylamidoborane complexes: mechanochemical synthesis, structure, stability, and reactive hydride composites. Issue 4 (31st January 2023) - Zhang, Ting; Steenhaut, Timothy; Li, Xiao; Devred, François; Devillers, Michel; Filinchuk, Yaroslav
Abstract : Na[Al(CH3 NHBH3 )4 ] and an intermediate Na[AlH(CH3 NHBH3 )3 ] were synthesized by ball milling. Na[Al(CH3 NHBH3 )4 ] + 12NaH/6NaNH2 released pure hydrogen at moderate temperatures, making this and similar systems interesting candidates for H-storage. Abstract : Methyl-substituted Al-based amidoborane Na[Al(CH3 NHBH3 )4 ] was designed and synthesized as a potential candidate for hydrogen-storage purposes. Its structure as well as that of Na[AlH(CH3 NHBH3 )3 ], forming as an intermediate in mechanochemical synthesis, were determined by high-resolution powder X-ray diffraction. The synthesis of Na[Al(CH3 NHBH3 )4 ] required the much cheaper CH3 NH2 BH3 and could be performed under less harsh conditions compared to the unsubstituted analogue. Na[AlH(CH3 NHBH3 )3 ] is the first example of an Al-based compound containing both hydride and amidoborane species. Despite Na[Al(CH3 NHBH3 )4 ] not being suitable for hydrogen storage on its own, reactive hydride composites (RHCs) made of Na[Al(CH3 NHBH3 )4 ] and 12 eq. of NaH, or 6 eq. of NaNH2, showed the release of pure hydrogen at moderate temperatures, making this and similar systems interesting candidates for hydrogen storage.